The Meaning of Space in Sign Language. Reference, Specificity and Structure in Catalan Sign Language Discourse - Barber (Sign Languages and Deaf Communities [SLDC], 2015)
Bringing together sign language linguistics and the semantics-pragmatics interface, this book focuses on the use of signing space in Catalan Sign Language (LSC). On the basis of small-scale corpus data, it provides an exhaustive description of referential devices dependent on space. The book provides insight into the study of meaning in the visual-spatial modality and into our understanding of the discourse behavior of spatial locations.